2018
DOI: 10.9734/ajaees/2018/28619
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Agricultural Livelihood Strategic Components in the Zambezi Region, Namibia

Abstract: This work was carried out in collaboration between both authors. Author JMN designed the study, collected the data and performed the statistical analysis. Author AB contextualized the analysis and provided meaning to it in the context of current developments in agricultural livelihood analysis. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Scholars agree that conservation is a significant constraint for agricultural development (Nyambe & Belete 2018;Gargallo 2020). This study provides an explanation for the exclusionary effects: commercial agriculture that would allow farmers to integrate into regional AVCs and lead towards relational upgrading is merely possible due to land insecurities, restricted water access and HWC.…”
Section: Development Trajectories and Resulting Policy Implicationsmentioning
confidence: 99%
“…Scholars agree that conservation is a significant constraint for agricultural development (Nyambe & Belete 2018;Gargallo 2020). This study provides an explanation for the exclusionary effects: commercial agriculture that would allow farmers to integrate into regional AVCs and lead towards relational upgrading is merely possible due to land insecurities, restricted water access and HWC.…”
Section: Development Trajectories and Resulting Policy Implicationsmentioning
confidence: 99%
“…Food crop production is dominated by those who attended just primary education (50 percent) and no formal education (38 percent). In Namibia, a study carried on agricultural livelihood strategies components confirmed that 35 percent had no formal education [14]. Food crop production is in the hands of those who ended their education at primary level or no education at all.…”
Section: Socioeconomic Characteristics Of Farmersmentioning
confidence: 99%